Plasmodium falciparum outbreak in native communities of Condorcanqui, Amazonas, Perú - Montenegro C.C. (2021)
Background: Malaria remains a serious health threat in the Amazonas Region of Peru and approximately 95% of the cases, mainly Plasmodium vivax, are found in native communities of The Rio Santiago District, Condorcanqui Province. In 2019, more than one thousand malaria cases were reported, with an unusual number of Plasmodium falciparum autochthonous cases. The present study aims to report this P. falciparum outbreak while describing the epidemiology of malaria and the risk factors associated in the native communities of Amazonas, Peru. Methods: The DIRESA-Amazonas in collaboration with the Condorcanqui Health Network and the Institute of Tropical Diseases of the UNTRM carried out a malaria Active Case Detection (ACD III) between January 31st and February 10th of 2020. A total of 2718 (47.4%) individuals from 21 native communities grouped in eight sanitary districts, were screened for malaria infections. Each participant was screened for malaria using microscopy. Follow-up surveys were conducted for all malaria positive individuals to collect socio-demographic data. Spatial clustering of infection risk was calculated using a generalized linear model (GLM). Analysis of risk considered factors such as gender, age, type of infection, symptomatology, and parasitaemia. Results: The study suggests that the P. falciparum index case was imported from Loreto and later spread to other communities of Rio Santiago during 2019. The ACD III reported 220 (8.1%) malaria cases, 46 P. falciparum, 168 P. vivax and 6 mixed infections. SaTScan analysis detected a cluster of high infection risk in Middle Rio Santiago and a particular high P. falciparum infection risk cluster in Upper Rio Santiago. Interestingly, the evaluation of different risk factors showed significant associations between low parasitaemia and P. falciparum asymptomatic cases. Conclusion: This is the first report of a P. falciparum outbreak in native communities of Condorcanqui, Amazonas. Timely identification and treatment of symptomatic and asymptomatic cases are critical to achieve malaria control and possible elimination in this area. However, the current malaria situation in Condorcanqui is uncertain, given that malaria ACD activities have been postponed due to COVID-19. © 2021, The Author(s).